Mesoporous Ce-doped Ti:Ash Photocatalyst Investigation in Visible Light Photocatalytic Water Pretreatment Process - Abdulkarim, Suliman; Ruzinah, Isha; Mazrul Nizam, Abu Seman; Abdul Latif, Ahmad; Jamil, Roslan (Department of Chemical Engineering, Diponegoro University, 2020)
The treatment of organic pollutants in water has been widely investigated including semiconductor photocatalysis is a promising approach to disinfect water. The objective of this study is to investigate the effect of Ce loaded on mesoporous Ti:Ash catalyst for water pretreatment process. The mesoporous Ti:Ash catalyst that doped with Ce was synthesised through wet impregnation method with 5%, 10% and 15% weight percentage of Ce doped on 40:60 Ti:Ash. The photocatalytic properties were characterized through X-ray powder diffraction, scanning electron microscopy with energy-dispersive X-ray spectroscopy, N2 adsorption-desorption studies and diffuse reflectance UV–vis absorption spectroscopy. It is found that the Ti:Ash nanocomposites doped with Ce shifted the light absorption band-edge position to the visible region. Moreover, the Ce doped Ti:Ash has large surface area and pore diameter. The Ce doping could significantly improve the absorption edge of visible light and adjust the cut-off absorption wavelength from 413 nm to 451, 477 and 496 nm for 5%, 10% and 15% Ce-doped mesoporous Ti:Ash catalysts, respectively. As the Ce doping ratio increased, the band gaps decreased from 3 eV to 2.48 eV. The most contaminant reduction up to 45% was achieved when Ti:Ash:Ce 40:55:5 was used. The higher Ce loading on the photocatalyst may reduce the photocatalyst performance because supernumerary metal loading on TiO2 can block TiO2 defect sites which are necessary for the adsorption and photoactivation. It can be deduced that the hybrid TiO2 photocatalyst that synthesized with OPFA and doped with Ce has huge potential to treat seawater.